Designing for Ideological Flexibility: Tracking Perspective Shifts in an Educational IDN - Pitt, Breanne; Youngblood, Wendy; Haahr, Mads (Springer, 2025)
This study investigates how interactive digital narratives (IDNs) can foster systems thinking and ideological flexibility in secondary learners by engag- ing them with ideologically diverse stakeholder perspectives. Grounded in the Context–Learning–Game (CLG) framework, the intervention integrates Emily Short’s Track Switching Choice structure and a non-playable character (NPC) functioning as a more-knowledgeable other (MKO) to scaffold learner engagement while exploring a complexity representation tool called Transformation Maps. Set within a simulated organizational debate on artificial intelligence, the narrative prompts learners to explore and synthesize viewpoints from three stakeholders. Behavioral data from gameplay logs, including perspective-switching frequency, time-on-task, and MKO interactions, were analyzed as indicators of ideological flexibility. Results show that most learners reconsidered their initial positions, with a significant number adopting more moderate viewpoints. Learners who switched perspectives spent more time in the experience, and MKO engagement strongly predicted final viewpoint change. A specific narrative moment, tagged Dhwani8, emerged as a cognitive inflection point associated with epistemic shift. These findings suggest that well-designed IDNs can reduce cognitive overload, support ideological exploration, and serve as analytic instruments for measuring learning behavior and epistemic development in complex decision-making contexts.
Lecture Notes in Computer Science
International Conference on Interactive Digital Storytelling (ICIDS) 2025
PUBLISHED
St Julian, Malta
Keywords: Systems Thinking; Interactive Digital Narrative; DSRP Framework; Zone of Proximal Development; Constructionism; Serious Game; Pedagogical Tools; Complex Systems; Creative Technologies; Digital Engagement; Digital Humanities